Multiphase renal CT in the evaluation of renal masses: Is the nephrographic phase necessary? - Songib, N.; Nazri, M.; Yaakup, N.; Nor, H.; Sun, Zhonghua (Elsevier Inc., 2013)
The aim of this study is to investigate the feasibility of eliminating the nephrographic phase from the four-phase renal computed tomography (CT) imaging to a three-phase protocol without affecting its diagnostic value. Thirty patients undergoing four-phase renal CT scans for assessment of renal lesions (>10 mm) were included in the study. A three-phase renal CT, without nephrographic phase, had similar diagnostic ability to a four-phase renal CT in the detection and characterization of renal lesions. A three-phase CT (plain, corticomedullary, and excretory phase) is therefore adequate in the clinical diagnosis of renal lesions.